To the problem of training of young volleyball players at the stage of initial training - Маклоуф [Muayad Maklouf] Муаяд (Slobozhanskyi Herald of Science and Sport, 2012)
The scientific and methodological literature on question of teaching methodology of young volleyball players at the stage of initial preparedness bearing in mind their level of physical qualities development is analyzed. Found that over the past years, the system of reserve training in volleyball is constantly changing due to a change of competition rules. The necessity of the development of new teaching techniques and methods of technical training volleyball players.